Implementasi Divisi Sumber Daya Manusia Dalam Pengelolaan Administrasi Dan Data Karyawan Pada PT Prima Perdana Mandiri Sidoarjo - Gwenda Vania Putri Nugroho; Siti Ning Farida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to describe the implementation of the Human Resources Division (HR) in managing administration and employee data at PT Prima Perdana Mandiri Sidoarjo. The HR Division has an important role in maintaining the smooth operation of the company through efficient administrative management and structured employee data management. The employee administration management process includes various activities such as recruitment, performance appraisal, attendance management, and employee development. On the other hand, employee data management is done by utilizing information technology, such as Human Resource Information System (HRIS), to store, process, and secure data effectively. The findings of this research show that the system implemented by PT Prima Perdana Mandiri drives the company's operational efficiency, maintains regulatory compliance, and provides a solid foundation for the company's future strategic planning.